Political Participation During Pandemic in the Local Election of Soppeng Regency, Indonesia - Rahma, Andi Aswirathul; Taufik, Ahmad; Hardi, Rudi; Alim, Irwan (Journal of Contemporary Local Politics, 2022)
This study aims to find out how the Political Participation of the Community in the Implementation of the 2020 Simultaneous Regional Elections in Soppeng Regency and also to find out the supporting and inhibiting factors of Community Political Participation in the Implementation of the 2020 Simultaneous Regional Elections. The type of research used is a qualitative research method and the type of research is descriptive. Data collection techniques using observation and interviews. The process of data analysis was carried out in several stages, namely checking all data, interview results, data reduction, presenting data and drawing conclusions. The results of the study show that the Political Participation of the Community in the Implementation of the 2020 Simultaneous Regional Head Elections in Soppeng Regency is influenced by several indicators, namely (1) Social and Economic Status. (2) Situation (3) Political awareness (4) Trust in the government. The supporting factor in public political participation is the political awareness of the community to choose its leader, while the inhibiting factors are bad weather, Covid-19, and the number of immigrants.